A note on the examination of Portugal’s hotels performance: a proposal for a new perspective’s approach - Freitas, N. M.; Filipe, J. A. (1st International Data Science & Engineering Proceedings & Abstract Book (IDSES’19), 2019)
The main objective of the present research paper is to give an exploratory vision on a new form of examining hotels’ performance of the Portuguese hotels’ market. This approach is based on the experience of a consultant in this area and is made in terms of revenue and occupancy, crossing then operational data with financial results. This analysis focuses on a recent period, since 2010 to 2017, involving the years since before and until after the big boom of tourism in Portugal. This paper exposes available data about hotels operational results and compares these results with hotels financial results. In terms of the evaluation of a hotel’s performance, the revenue per available room (RevPAR) is regarded by the tourism industry and INE (the Portuguese National Statistics Institute) as the most important measure, once it compares hotels among themselves and also compares regions. An important aspect of this study is highlighting the limitations of RevPAR.